Exploring maize grain yield response to boron fertilization in Mollisols : critical thresholds and predictive models - Barbieri, Pablo (2024)
Background: There are no extractable boron (B) thresholds for maize (Zea mays L.) in Mollisols determined by field calibrations. Aims: Our objectives were to: (1) explore maize grain yield response to B fertilization, (2) calibrate the soil hot water extractable B (HW-B) as a predictor of maize response to B fertilization under field conditions, and (3) assess the contribution of clay, pH, and soil organic matter (SOM) as predictive variables of maize response to B fertilization. Methods: We conducted 53 field trials with 2 treatments: with and without B fertilization. At all sites, we measured clay, SOM, pH, and HW-B at a 0–20 cm depth. Results: Maize grain yield ranged from 5.34 to 17.35 Mg ha−1. Grain yield response to fertilization was observed in 6 out of 53 sites (11.3%). In responsive sites, average grain yield response was 1.0 Mg ha−1. Multiple regression models to predict yield response to B addition that included soil, pH, and SOM only explained 19% of the variability. The critical soil HW-B concentration threshold was 0.78 mg kg−1, correctly diagnosing 79% of the site-years. Conclusion: The critical threshold for maize B levels resulting from our field study is the first of its kind in Mollisols. This threshold will improve the identification of soils deficient in B.